2019
DOI: 10.3390/nano10010049
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive SERS-Based Plasmonic Sensor with Analyte Enrichment System Produced by Direct Laser Writing

Abstract: We report an easy-to-implement device for surface-enhanced Raman scattering (SERS)-based detection of various analytes dissolved in water droplets at trace concentrations. The device combines an analyte-enrichment system and SERS-active sensor site, both produced via inexpensive and high-performance direct femtosecond (fs)-laser printing. Fabricated on a surface of water-repellent polytetrafluoroethylene substrate as an arrangement of micropillars, the analyte-enrichment system supports evaporating water dropl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 73 publications
(93 reference statements)
0
33
0
Order By: Relevance
“…It was demonstrated that the SERS effect on LIPSS on polymers that were overcoated with gold can increase the detection sensitivity of specific analyte molecules by several orders of magnitude [ 95 , 96 ]. Additionally, the localized laser surface processing could help to spatially confine the analyte solution during an additional evaporation-based concentration enhancement step [ 97 , 98 ]. Magnetic and superconducting properties of LIPSS: Several authors started to investigate the impact of LIPSS on magnetic [ 99 , 100 , 101 ] and superconducting properties [ 102 ].…”
Section: Recent (Ongoing) Trendsmentioning
confidence: 99%
“…It was demonstrated that the SERS effect on LIPSS on polymers that were overcoated with gold can increase the detection sensitivity of specific analyte molecules by several orders of magnitude [ 95 , 96 ]. Additionally, the localized laser surface processing could help to spatially confine the analyte solution during an additional evaporation-based concentration enhancement step [ 97 , 98 ]. Magnetic and superconducting properties of LIPSS: Several authors started to investigate the impact of LIPSS on magnetic [ 99 , 100 , 101 ] and superconducting properties [ 102 ].…”
Section: Recent (Ongoing) Trendsmentioning
confidence: 99%
“…The laser pulse driven avalanche ionisation of gold is seeding the energy deposition which is evolving into run away ablation (melting, evaporation, ionisation). The general geometry of the surface structure produced by direct laser ablation is defined by the laser irradiation parameters (fluence, pulse width and beam profile [46]) as well as by the thickness/composition of the metal film [33,47]. Our results clearly show that advanced chemical engineering of the metal film composition gives additional degree of freedom allowing to modify morphology of the laser-printed structures at the nanoscale, namely, incorporate the nanopores and control their density.…”
Section: Aumentioning
confidence: 78%
“…The SERS spectra were collected using 10 accumulations and an acquisition time of 1 s per measurement. The background noise and fluorescence in the Raman measurements were automatically corrected by the instrument software algorithm (OceanView Spectroscopy 1.5.07, Dunedin, FL, USA) [ 16 , 22 ]. The high-performance liquid chromatography (HPLC) measurements were carried out using Agilent HPLC Series 1100 with a Diode array detector (Waldbronn, Germany) and the detector was set at 298 nm.…”
Section: Methodsmentioning
confidence: 99%
“…For example, highly ordered metallic substrates have been fabricated using lithographic, chemical ion etching, and picosecond/femtosecond laser ablation techniques to provide reproducible SERS measurements [ 11 , 14 ]. Other methods, such as direct laser writing and electrochemical deposition, have been also used to synthesize randomly patterned substrates for the detection of various analytes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%